El fantasma de la infidencia. Expresiones antimonárquicas en Nueva España en vísperas de la independencia (Tzintzun, Revista de Estudios Históricos, 2016)
This paper examines the social and political environment in New Spain in the wake of the French occupation of Spain in 1808. It analyzes 16 trials against individuals accused of breaching the trust of the Spanish Monarch. Such trials were led by the junta de seguridad y buen orden, a special tribunal created by the viceroy-archbishop Francisco Xavier Lizana y Beaumont in 1809. The article highlights the climate of fear and the widespread fidelity toward the Monarch generated by the French invasion. It also shows how the collective mentality operated during this period of crisis.
Keywords: breach-of-trust; junta de seguridad; fidelity; fear; Fernando vii